PRINSIP KESANTUNAN BERBAHASA PADA MAKSIM KEARIFAN DI DALAM KOLOM KOMENTAR AKUN INSTAGRAM NADIEM MAKARIM DI POSTINGAN HARI GURU SEDUNIA - Sari, Muliana; Ningsih, Rika (Universitas Muhammadiyah Tapanuli Selatan, 2023)
Language politeness is essentially an ethic of socializing in society. When speaking is done politely, a person is able to maintain his own dignity and respect for others. Politeness of a person can also be seen from the use of language. Language is principally a tool for communicating and exchanging information with the interlocutor. A language process is said to be running well if the meaning conveyed by the speaker to the interlocutor can be understood and does not cause misinterpretation. Maxims are principles that must be obeyed by speech participants in interacting, both textually and interpersonally in expediting the course of the communication process. The problem studied in this study is how politeness in the language of netizens applies to the maxim of wisdom in the comments column on the World Teacher's Day post on Nadiem Makarim's Instagram account. The purpose of this study is to find out politeness in the language of netizens on the maxim of wisdom in the comments column on World Teacher's Day posts on Nadiem Makarim's Instagram account. The main theory used in this research is Leech's theory. The research data is in the form of comments from netizens that contain the maxim of wisdom contained in the comment column on Nadiem Makarim's Instagram account. The approach used is a qualitative approach. The method used is content analysis method. Data collection techniques that the authors use are documentation techniques, reading techniques and note-taking techniques. The data analysis technique that the author uses is content analysis technique or content analysis. The research results obtained in the principle of politeness in the maxim of wisdom in the comments column of Nadiem Makarim's Instagram account in the World Teacher's Day post, namely that there were as many as 30 utterances included in the maxims of wisdom.